Design of a new UTC-PD to enhance the BW value - Gencal, Huriye; Öztürk, Turgut (Institute of Electrical and Electronics Engineers Inc., 2021)
Promising UTC-PDs have been actively used recently in terms of being an alternative to expensive and bulk THz resources used in many areas such as millimeter and Terahertz (THz) signal (wave) production, communication, imaging and spectroscopy. A new product has been developed by modifying the geometric structure of UTC-PD, which has features such as room temperature usage, high operating speed and high operating frequency. The most important feature of the design is that it performs successfully in 0 (zero) Volt, in other words zerobias, applications and has approximately three times more bandwidth than its equivalent.
BW degerini artırmak için yeni bir UTC-PD tasarımı
Keywords: Millimeter wave; Millimeter/Terahertz communication; Photodiode; Terahertz; Terahertz radiation; Terahertz source; THz signal generetion; Zero-bias